Physics Teachers’ Pedagogical Content Knowledge (PCK) in Developing Content Representation (CoRe) on the Topic of Classical Mechanics - Muhammad Miftakhul Falah; Hartono Hartono; Sunyoto Eko Nugroho; Saiful Ridlo (International Conference on Science, Education, and Technology, 2021)
This study aims to describe physics teachers' ability to represent their content knowledge and pedagogy on classical mechanics concept using a CoRe framework in teaching practice, and to figure out their ability to develop the CoRe according to the length of teaching experiences, educational levels, and gender. The data were collected by reviewing the CoRe documents created by 40 high school physics teachers in Central Java and the Yogyakarta Special Region as a part of in-service training activities. The RASCH model was employed to analyze the research data, both qualitatively and quantitatively. The results of the study revealed that teachers were able to develop the CoRe with high qualification (76,1%). There was no teacher with poor and even fail categories. The ability to develop the CoRe will support them in designing a classroom learning. The aspect that requires improvement is the statement about outlining the material structures that will be delivered to students based on their mastery levels. The findings employing the DIF analysis showed that the length of teaching experiences had an effect on differences in the ability to develop the CoRe on the aspects of big idea development, material choices and sequences of delivery. Nevertheless, the ability of male and female teachers to develop CoRe is relatively similar. Meanwhile, physics teachers with master degree have better identification skills and procedures for the significance of big idea development than those with bachelor degree do.